Early Rhythm Control Therapy in Patients With Atrial Fibrillation and Heart Failure. Issue 11 (30th July 2021) - Rillig, Andreas; Magnussen, Christina; Ozga, Ann-Kathrin; Suling, Anna; Brandes, Axel; Breithardt, Günter; Camm, A. John; Crijns, Harry J.G.M.; Eckardt, Lars; Elvan, Arif; Goette, Andreas; Gulizia, Michele; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Even on optimal therapy, many patients with heart failure and atrial fibrillation experience cardiovascular complications. Additional treatments are needed to reduce these events, especially in patients with heart failure and preserved left ventricular ejection fraction. Methods: This prespecified subanalysis of the randomized EAST-AFNET4 trial (Early Treatment of Atrial Fibrillation for Stroke Prevention Trial) assessed the effect of systematic, early rhythm control therapy (ERC; using antiarrhythmic drugs or catheter ablation) compared with usual care (allowing rhythm control therapy to improve symptoms) on the 2 primary outcomes of the trial and on selected secondary outcomes in patients with heart failure, defined as heart failure symptoms New York Heart Association II to III or left ventricular ejection fraction [LVEF] <50%. Results: This analysis included 798 patients (300 [37.6%] female, median age 71.0 [64.0, 76.0] years, 785 with known LVEF). The majority of patients (n=442) had heart failure and preserved LVEF (LVEF≥50%; mean LVEF 61±6.3%), the others had heart failure with midrange ejection fraction (n=211; LVEF 40%–49%; mean LVEF 44 ± 2.9%) or heart failure with reduced ejection fraction (n=132; LVEF<40%; mean LVEF 31±5.5%). Over the 5.1-year median follow-up, the composite primary outcome of cardiovascular death, stroke, or hospitalization for worsening of heart failure or for acute coronary syndrome occurred less often in patients randomly assigned to ERC (94/396; 5.7 per 100 patient-years) compared with patients randomly assigned to usual care (130/402; 7.9 per 100 patient-years; hazard ratio, 0.74 [0.56–0.97]; P =0.03), not altered by heart failure status (interaction P value=0.63). The primary safety outcome (death, stroke, or serious adverse events related to rhythm control therapy) occurred in 71 of 396 (17.9%) patients with heart failure randomly assigned to ERC and in 87 of 402 (21.6%) patients with heart failure randomly assigned to usual care (hazard ratio, 0.85 [0.62–1.17]; P =0.33). LVEF improved in both groups (LVEF change at 2 years: ERC 5.3±11.6%, usual care 4.9±11.6%, P =0.43). ERC also improved the composite outcome of death or hospitalization for worsening of heart failure. Conclusions: Rhythm control therapy conveys clinical benefit when initiated within 1 year of diagnosing atrial fibrillation in patients with signs or symptoms of heart failure. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01288352. URL: http://www.controlled-trials.com ; Unique identifier: ISRCTN04708680. URL: https://www.clinicaltrialsregister.eu ; Unique identifier: 2010-021258-20.